2020
DOI: 10.1002/bsd2.123
|View full text |Cite
|
Sign up to set email alerts
|

Does remittance inflow influence human development in south Asian countries? An empirical insight

Abstract: This article investigate the relationship between human development, remittance inflows, and other macroeconomic variables like life expectancy, human capital, FDI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Some of these have analyzed the determinants of remittance (Akcay and Karasoy 2019b;El-Sakka and McNabb 1999;Mayda 2010;Al-Mashat and Billmeier 2012). Several others have examined the linear or nonlinear effect of remittance on macroeconomic fundamentals such as economic growth (Cooray 2012;Jawaid and Raza 2012;Olayungbo and Quadri 2019;Olayungbo et al 2020;Das and Sethi 2019;Karikari et al 2016;Imai et al 2014;Koay and Choong 2013), human development (Adenutsi 2010;Sahoo and Sethi 2021;Sahoo et al 2020), export and trade balance (Farzanegan and Hassan 2016;Jena and Sethi 2019), and electricity consumption (Akcay and Demirtas 2015;Sahoo and Sethi 2019).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Some of these have analyzed the determinants of remittance (Akcay and Karasoy 2019b;El-Sakka and McNabb 1999;Mayda 2010;Al-Mashat and Billmeier 2012). Several others have examined the linear or nonlinear effect of remittance on macroeconomic fundamentals such as economic growth (Cooray 2012;Jawaid and Raza 2012;Olayungbo and Quadri 2019;Olayungbo et al 2020;Das and Sethi 2019;Karikari et al 2016;Imai et al 2014;Koay and Choong 2013), human development (Adenutsi 2010;Sahoo and Sethi 2021;Sahoo et al 2020), export and trade balance (Farzanegan and Hassan 2016;Jena and Sethi 2019), and electricity consumption (Akcay and Demirtas 2015;Sahoo and Sethi 2019).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Huay et al (2019) found that the effect of remittances was statistically significant with positive coefficients in 67 developing economies. Sahoo et al (2020) found the positive effect of remittance on human development in South Asian countries. Ali Bare et al (2022) examined the effect of remittances on human capital development in sub-Saharan Africa.…”
Section: Literature Review Linking Remittance and Sedmentioning
confidence: 98%
“…This study finds that remittances positively impact the human capital formation in developing countries. Sahoo et al (2020) investigates the relationship between inflows of remittances and human capital in South Asia during 1990-2018. The Fisher residual cointegration technique, vector error correction mechanism, fully modified OLS and dynamic OLS techniques were applied in this study.…”
Section: Empirical Literaturementioning
confidence: 99%